« Li chivalier se desportoient / Lai ou dames les apeloient. » Exemples de circulation des premiers vers d’Yvain ou le Chevalier au lion - Sofia Lodén; Vanessa Obry (Atalaya)
This article discusses the first folio of the Lyon manuscript of La Chanson de Roland, in which the battle of Roncevaux is preceded by the first ten verses of Chrétien de Troyes’ Yvain ou le Chevalier au lion. These verses about King Arthur and his court function as an introduction to what follows and influence the reading of the chanson de geste. By comparing the opening of Chrétien’s romance to that of the German, Old Norse, Swedish and French renaissance adaptations of Le Chevalier au lion, we can see how Chrétien’s prologue changes from one context to another, while the need to refer to an authority remains unchanged. In the Nordic adaptations, Charlemagne is the starting point in the presentation of King Arthur, attesting the need to introduce Arthur to an audience that does not know him. In the Lyon manuscript it is the other way around: Arthur and his court are the starting point for a story about Charlemagne and his battles, adapting the chanson to new needs and expectations. In both cases, it is the king – Charlemagne or Arthur – who brings authority to the other king and to the texts themselves. In the Lyon manuscript, the picture of the court, in which stories are told, replaces the orality of the chanson de geste. Chrétien’s prologue, atypical of its author, is thus given a new role, that of a standard prologue.